HUBUNGAN ANTARA PENERAPAN PROGRAM SANITASI TOTAL BERBASIS MASYARAKAT (STBM) DENGAN KEJADIAN DIARE DI WILAYAH KERJA PUSKESMAS JATIBOGOR KABUPATEN TEGAL - Dinar Andaru Mukti; Mursid Raharjo; Niki Astorina Yunita Dewanti (Jurnal Kesehatan Masyarakat (Undip), 2016)
The occurrence of diarrhea is still high and the top 10 diseases in Jatibogor Health Center, in line with poor sanitary conditions, especially the behavior of open defecation which reached 30% of the population. The goal of this study is to determine the relationship between the implementation of CLTS program with the occurance of diarrhea in Jatibogor Public Health Center Tegal. This study is an observational analytic research with cross sectional approach. This study population is all households living in Jatibogor Public Health Center Tegal. The sample is 100 households. The sampling technique using proportional random sampling. Data analysis using chi square test. The results of this study indicate that 22% of households defecation carelessly, 50% do not apply handwashing with soap, 51% do not apply drinking water and food management, 97% do not apply safe waste management, and 94% do not apply safe waste water management. There is a relationship between the implementation of STBM in stop open defecation aspect (p=0,02), handwashing with soap aspect (p=0,013), and household waste water management aspect (p=0,047) with the occurrence of diarrhea in Jatibogor Public Health Center Tegal. There is no relationship between the implementation of STBM in household drinking water and food management aspect (p=0,570) and household waste management aspect (p=0,636) with the occcurance of diarrhea in Jatibogor Public Health Center Tegal. The implementation of STBM program associated with the occurance of diarrhea in Jatibogor Public Health Center Tegal in aspects stop defecating carelessly, washing hands with soap, and waste water management.